EFFECT OF IRRIGATION LEVELS AND WEED MANAGEMENT ON PRODUCTIVITY OF WHEAT (TRITICUM AESTIVUM, L.) UNDER ZERO TILLAGE - YAGHOBI, GHOLAM ALI; SHARMA, G.L. (Annals of Agricultural Research, 2014)
An experiment was carried out during rabi, 2007-08 at the Instructional Farm, Department of Agronomy, RCA, Udaipur. The experiment comprised combinations of four levels of irrigation based on IW/CPE ratio (0.5. 0.75, 1 .0 and 1 .25 IW/CPE with 6 cm water) in main plots and four weed control methods (weedy check,pendimethalin at 0.75 kg/ha as pre-emergence, combination of 2.4-D at 0.4kg/ha + isoproturon at 0.6 kg/ha as post- emergence and manual weeding at 35 DAS) in sub plots, replicated thrice.The results Â showed that varying irrigation levels from 0.5 to 1.25 IW/CPE recorded increases in weed dry matter. Irrigation at 1.25 IW/CPE with 6 cm was observed at par with 1 .0 IW/CPE and both these levels recorded significantly higher number of effective tillers/m, number of grains per ear, test weight of grains, grain and biological yield and consumptive use over irrigation at 0.5 and 0.75 IW/CPE.